Empoderamento de meninas : a dimensão do espaço escolar no processo de emancipação feminina para além dos muros da escola - França, Anelize Castedo (2020)
This research is based on the following questions: What does power mean for girls? Do your perceptions lead to empowerment? The general objective sought to analyze the meanings of power from the conceptions of high school girl students and to know if their perceptions lead to empowerment. The specific objectives were: to understand the theoretical production of feminist and gender studies with a focus on the post-structuralist approach; understand the concept of empowerment from feminist literature; identify the profile of girls students from the analysis of socioeconomic and ethnic-cultural survey and documents available at school; verify, in the quantitative data, the aspects that may indicate empowerment; and to interpret the participants' narratives with emphasis on the most relevant aspects of the research problem. The methodological resources used in the data collection consisted of the application of socioeconomic and ethnic-cultural surveys, conversation circles and individual interviews, mediated by semi-structured questions and documents available at school, such as the PPP (Political-Pedagogical Project) and medical records (notebooks of classes). As a theoretical reference for this work, the emphasis was on the post-structuralist approach, due to its close connection with feminist theories, gender theories, discourse theory, cultural studies and queer theory, and one of its premises is the criticism directed at the centered subject, built by modernism and humanism from the negation of the other, which escapes the notion of normality. The results of the research partially confirmed the hypothesis that the conception of power is linked to the condition of recognizing the dimension of their capacities from the questioning of existing social patterns in interface with social interactions, insofar as they re elaborate behaviors and identities favorable to empowerment condition. The analysis of the quantitative data and the content of the speeches demonstrated that their experiences intertwine in a timid subversion and the maintenance of a status quo, and, therefore, we defend the existence of a possible hybridism: neither so empowered nor so subjected. This process of uncertainty is in constant propensity, both for the first and for the second. Therefore, the dialogue on gender issues at school is of a sustainable nature, as it can contribute to the “performatization” of empowered identities compatible with a plural and fully human society.